The management structure review. A dialectical interpretation: implications for higher education - Rodríguez Matos, José M. (2011)
This presentation will elaborate and explain core concepts that clarifypropositions and approaches thatI do in the book The management structure review: a dialectical interpretation. Similarly, I will analyze how these concepts help to understand the dialectic paradigm of management reviewI propose in this book. analyze,addition, the implications of this paradigm for the management of higher education.